1983
DOI: 10.1111/j.1365-3024.1983.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the growth and differentiation of Trypanosoma (Trypanozoon) brucei brucei in resistant (C57B1/6) and susceptible (C3H/He) mice

Abstract: While Trypanosoma brucei brucei GUTat 3 were equally infective for C3H/He and for C57Bl/6 mice at doses ranging from 5 to 5 x 10(3) organisms and had similar prepatent periods in both strains of mice, infected C57Bl/6 mice displayed lower parasitaemia, shorter times to parasite wave remission and survived for a longer time than infected C3H/He mice. Parasite growth and differentiation rates and host immune responses were similar for the first 5 days in both strains of mice after infection with 10(3) T.b.brucei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 17 publications
1
23
1
Order By: Relevance
“…Thus, if antibody responses were responsible for these observations the functional activity of the antibody response would have had to increase by the same proportion with each 10-fold increase in inoculum size. Such a linear relationship between the antibody response and the quantity of trypanosome antigen is inconsistent with experimental findings (8). Furthermore, by extrapolation from experiments carried out with cattle, it would appear that the smallest inoculum sizes used in our experiment would be insufficient to elicit an anti-variant-specific surface glycoprotein response (32).…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Thus, if antibody responses were responsible for these observations the functional activity of the antibody response would have had to increase by the same proportion with each 10-fold increase in inoculum size. Such a linear relationship between the antibody response and the quantity of trypanosome antigen is inconsistent with experimental findings (8). Furthermore, by extrapolation from experiments carried out with cattle, it would appear that the smallest inoculum sizes used in our experiment would be insufficient to elicit an anti-variant-specific surface glycoprotein response (32).…”
Section: Discussioncontrasting
confidence: 81%
“…The maximum concentration that a trypanosome population attains in rodents is regulated by both host factors (7,8) and host-independent mechanisms associated with the parasite population (9). The results described here have demonstrated that diminazene susceptibility is dependent upon the concentration of a trypanosome population in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistant strains of mice have earlier and higher serum anti-VSG antibody response than susceptible strains (Black et al 1983, Whitelaw et al 1983, Mitchell & Pearson 1986). Because it has been shown that nude mice infected with T. brucei rhodesiense were capable of controlling their first wave of parasitaemia (Campbell, Esser & Philips 1978), one could argue that an IgM anti-VSG antibody response is sufficient to control variant specific parasitemia (Mansfield 1990).…”
Section: Introductionmentioning
confidence: 94%